320-detector-row computed tomography arteriography using CO2 gas to detect malignant liver tumors. Issue 2 (April 2012) - Sonoda, Akinaga; Nitta, Norihisa; Ushio, Noritoshi; Nitta-Seko, Ayumi; Tomozawa, Yuki; Watanabe, Shoubu; Ohta, Shinichi; Takahashi, Masashi; Murata, Kiyoshi
Abstract Purpose: We present the initial steps for 320-detector-row computed tomography arteriography using CO2 gas (320-MDCT CO2 arteriography) to detect the vascular area of malignant liver tumors. Material and methods: This study was approved by the Ethics Committee of our institution. Written prior informed consent was obtained from all patients. We studied six patients with primary and metastatic liver tumors (n = 26) and allergic reactions to iodinated contrast media or a tendency for renal failure. CO2 was injected at 1 ml/sec (volume 8 ml) into the common hepatic artery and a CT scan was acquired 12 seconds after the start of injection. The detection of the vascular area of the tumor or of intratumor air was evaluated with respect to the relationship between the size and location of the tumors. Cramer's V statistic was performed to explore the relationship (p < 0.05). Results: The vascular area was detected in 17 of the 26 tumors (65.4%). There was a correlation between the detection of the adjacent vascular area on CTA images acquired with the use of CO2 and the tumor site observed on previously-acquired MRI or CT images. Conclusion: 320-MDCT CO2 arteriography with microcatheters may be useful for the detection of the vascular area.